ESPN Thematic Report on National strategies to fight homelessness and housing exclusion - Finland - Olli Kangas; Laura Kalliomaa-Puha (European Commission, 2022)
Finland is among the few EU Member States that have managed to significantly reduce homelessness in last two to three decades. In 1987, the number of homeless people was 18,000. This number dropped to 10,000 in 1995, and in 2018 there were only 5,482 homeless people in Finland. Since there is a significant overlap between the EU-ETHOS and national classifications, this decreasing trend is evident regardless of whether we use ETHOS Light definitions or national definitions.
This success is the result of several factors. Fighting homelessness is a national strategy rather than a local activity or a charity project. Indeed, combatting homelessness has become a shared goal, bringing together NGOs, municipalities and the government. In the 2000s, the state launched and funded programmes aimed at reducing homelessness, which in particular tackled the situation of the most vulnerable long-term homeless people. With the help of these programmes, organisations and municipalities have provided new housing for homeless people and improved their services. The whole system is now built on the Housing First principle. The Housing First principle states that when addressing the various problems that homeless people are facing, the first support measure should always be the provision of housing. This can be achieved using various models and by providing different kinds of housing, but housing is always the top priority.
The biggest group of homeless people are those who are temporarily residing with friends and relatives: in 2018, 76% of all homeless people belonged to this category. Demographically, single males are the most likely to be homeless. One of the main drivers of homelessness in this group is alcoholism and drug abuse. About one fifth of single homeless people are younger than 25, and one fourth have an immigrant background. Paperless immigrants (undocumented immigrants), in particular, are at a high risk of homelessness. While the number of homeless immigrants in 2003 was about 250, the corresponding number in 2017 was as high as 1,700.
With regards to homeless families, single parents are strongly over-represented: as many as 77.4% of homeless families are single-parent households. Immigrant families are also over-represented in this category (39.0% of all homeless families).
Measures to reduce homelessness take on many different forms (producing new flats, emergency accommodation, supported housing, other housing services, housing advice, organising networks where public, private and NGOs cooperate) and vary depending on the target group in question (young people, immigrants, people leaving prison, people with mental health problems, drug abusers etc.). So far, the Finnish model of service production (services in-kind and in-cash) has been a success story.
However, the Finnish system also has weaknesses. In some subcategories of homelessness, the quality of the services may be good, but there is a shortage in the quantity of services. In particular, this is the case with services for prisoners and services targeted at immigrants. With regard to homeless people who suffer from mental health problems or who are substance abusers, there need to be more services and the services need to be better in terms of their quality and efficiency.
One of the main weaknesses in the Finnish housing policy is a lack of affordable rental apartments. Immigrants and paperless people (undocumented immigrants), in particular, are in a vulnerable position. Their situation often leads to poverty and homelessness. Here, the priority should be to improve the asylum-seeking process and, if necessary, to grant permission to reside in the country for humanitarian reasons.